Gender representations in advertising narratives in the Republic of Serbia - Ocokoljić Marija (Marketing (Beograd. 1991), 2022)
Perceptions of gender roles are a result of socialization processes happening under the influence of diverse cultural factors. One of the strongest shaping forces in that context are mass media, and within them, advertising. In the executed research it is treated as a domain actively participating in the creation of cultural gender normative. Key research question is focused on gender representations in advertising. An ad is treated as a cultural text transferring not only commercial, but also wider cultural meanings. Content analysis applied to the selected advertising content broadcasted in the Republic of Serbia showed that quantitatively larger representation and visibility of women does not necessarily mean their actual greater significance. Some traditional patterns are changing. Other however are persisting. In areas like family, household and children care, advertising practices are evolving. More content shows both genders working together (caring for children, preparing food etc.). Men are represented as more active participants of family life. On the other hand, traditional pattern of representing women in the context of the body, beauty, physique is not changing much. They are more frequently in decorative and passive roles which is a dimension of representation nonexistent with men.